Fiscal Compliance and Fiscal Response to the COVID-19 Crisis in Visegrad and Baltic States - Dmytrenko, Denys; Provazníková, Romana (Univerzita Pardubice, 2023)
The coronavirus crisis, which began in 2020, had a major impact on the fiscal policies of the EU member states. Governments increased their spending to support economies affected by quarantine measures. Expenditure increase and revenue reduction made EU countries non-compliant with the requirements set by the Stability and Growth Pact, adopted to balance fiscal policies. However, countries were affected differently and used different fiscal measures. The paper discusses differences in fiscal response to the COVID-19 crisis among Baltic and Visegrad countries. The paper aims to analyse how the fiscal response in 2020 correlates with their fiscal indicator's compliance in the pre-crisis period (2004-2019). The results suggest that the states could be divided into two subgroups according to their fiscal stance before 2020 and their reactions to the shock. The first group, consisting of Hungary, Poland, and Slovakia, represent states with a higher level of public debt, lower compliance with the debt and deficit rules, and higher expenditures. Hungary stands out among the states, while Estonia and the Czech Republic have the best compliance scores.
Dodržování fiskálních pravidel a fiskální reakce na krizi COVID-19 ve visegrádských a pobaltských zemích
Keywords: Fiscal Reactions; Fiscal Rules; Fiscal Compliance; COVID-19 crisis; Correlation Analysis; Fiskální reakce; fiskální pravidla; dodržování fiskálních pravidel; krize COVID-19; korelační analýza